Impact of Linker Modification and PEGylation of Vancomycin Conjugates on Structure-Activity Relationships and Pharmacokinetics - Florian Umstätter; Julia Werner; Leah Zerlin; Eric Mühlberg; Christian Kleist; Karel D. Klika; Tobias Hertlein; Barbro Beijer; Cornelius Domhan; Stefan Zimmermann; Knut Ohlsen; Uwe Haberkorn; et al. (MDPI AG, 2022)
As multidrug-resistant bacteria represent a concerning burden, experts insist on the need for a dramatic rethinking on antibiotic use and development in order to avoid a post-antibiotic era. New and rapidly developable strategies for antimicrobial substances, in particular substances highly potent against multidrug-resistant bacteria, are urgently required. Some of the treatment options currently available for multidrug-resistant bacteria are considerably limited by side effects and unfavorable pharmacokinetics. The glycopeptide vancomycin is considered an antibiotic of last resort. Its use is challenged by bacterial strains exhibiting various types of resistance. Therefore, in this study, highly active polycationic peptide-vancomycin conjugates with varying linker characteristics or the addition of PEG moieties were synthesized to optimize pharmacokinetics while retaining or even increasing antimicrobial activity in comparison to vancomycin. The antimicrobial activity of the novel conjugates was determined by microdilution assays on susceptible and vancomycin-resistant bacterial strains. VAN1 and VAN2, the most promising linker-modified derivatives, were further characterized in vivo with molecular imaging and biodistribution studies in rodents, showing that the linker moiety influences both antimicrobial activity and pharmacokinetics. Encouragingly, VAN2 was able to undercut the resistance breakpoint in microdilution assays on vanB and vanC vancomycin-resistant enterococci. Out of all PEGylated derivatives, VAN:PEG1 and VAN:PEG3 were able to overcome vanC resistance. Biodistribution studies of the novel derivatives revealed significant changes in pharmacokinetics when compared with vancomycin. In conclusion, linker modification of vancomycin-polycationic peptide conjugates represents a promising strategy for the modulation of pharmacokinetic behavior while providing potent antimicrobial activity.